Verkehrsmanagement für Großveranstaltungen. Fußball WM 2006: Leistungskatalog in Frankfurt a.M. Major events' traffic management in connection with the 2006 Football World Championship. - Pullmann, Nora; Scherz, Susanne; Schuster, Bernd; Sturm, Peter (Deutscher Verkehrs-Verl., 2006)
Im Sommer 2006 findet in Deutschland die FIFA Fußball-Weltmeisterschaft statt. Eine der zwölf Austragungsstätten ist das Stadion in Frankfurt am Main. Die Vorbereitungen für das Großereignis laufen in der Region Frankfurt RheinMain auf Hochtouren. Es wird ein Leistungskatalog vorgestellt, der als Methodik für die Organisation und Durchführung von Großereignissen am Beispiel der WM 2006 entwickelt wurde. difu

The Football World Championship of 2006 has prompted the Frankfurt Rhein-Main Region to compile a 'catalogue of tasks' that is intended to facilitate the organization and handling of very big events. This guide details the relevant responsibilities, scale of operation and all the basic requirements neede to ensure the effective coordination of event-related special tasks, and of all the participation bodies. This catalogue is continually improved and updated, and is intended to be a working tool and essential guide for the coordinating body 'Transport & Verkehr'. The methodology applied to this catalogue may helb plan and control big events in future. difu
Keywords: Öffentlicher Verkehr; Verkehrsplanung; Regionalverkehr; Verkehrssicherheit; Mobilität; Sport; Sportveranstaltung; Großveranstaltung